The recognition and negotiation of class-based barriers to progression and inclusion in accounting professional services firms - Flanagan, Christopher; Joyce, Yvonne (Accounting, Organizations and Society, 2024)
Drawing on interviews with accountants working at professional services firms (PSFs) in the UK, we explore how reflexivity enables accountants to recognise and negotiate class-based barriers to progression and inclusion. We identify a range of reflexive practices (including conversations with colleagues and clients, observations, mentoring, mulling over, and imagining) and show how these interact with habitus to structure the individual (mis)recognition of class-based barriers in the workplace. We find that reflexivity can engender an awareness of ‘difference’ and sense of inferiority relative to others, primarily for those from less privileged backgrounds. We provide evidence of the enabling role of reflexive practices which lead to purposive action for negotiating class-based barriers. However, we also find that reflexivity can lead to idiosyncratic strategies which support assimilation to (rather than challenging) existing practices in the accounting field. We find contradictory accounts of the effects of class, where class is recognised as a barrier, yet individuals are thought to progress through merit. We explain this tension through the limitations of reflexivity, restricted opportunities for reflexivity, and misrecognition of the effects of class in a seemingly meritocratic system. We provide examples of enduring and unrecognised class-based inequalities in accounting PSFs, including team composition and work allocation, class-segmented service lines, and the long-term consequences for those from less privileged backgrounds of having to work harder to ‘reach the same level’. Our findings suggest that PSFs must facilitate ‘difficult’ conversations aimed at breaking the culture of silence around class.